Role of PCNA and TLS polymerases in D-loop extension during homologous recombination in humans - Sebesta, Marek; Burkovics, Peter; Juhasz, Szilvia; Zhang, Sufang; Szabo, Judit E; Lee, Marietta Y W T; Haracska, Lajos; Krejci, Lumir (DNA repair, 2013)
Homologous recombination (HR) is essential for maintaining genomic integrity, which is challenged by a wide variety of potentially lethal DNA lesions. Regardless of the damage type, recombination is known to proceed by RAD51-mediated D-loop formation, followed by DNA repair synthesis. Nevertheless, the participating polymerases and extension mechanism are not well characterized. Here, we present a reconstitution of this step using purified human proteins. In addition to Pol δ, TLS polymerases, including Pol η and Pol κ, also can extend D-loops. In vivo characterization reveals that Pol η and Pol κ are involved in redundant pathways for HR. In addition, the presence of PCNA on the D-loop regulates the length of the extension tracks by recruiting various polymerases and might present a regulatory point for the various recombination outcomes.
Keywords: osmolární koncentrace; proliferační antigen buněčného jádra; DNA Damage; DNA, Single-Stranded; DNA repair synthesis; DNA-polymerasa iota; DNA-Directed DNA Polymerase; DNA Replication; replikace DNA; Homologous Recombination; poškození DNA; HeLa Cells; rekombinasa Rad51; Osmolar Concentration; DNA Polymerase iota; Proliferating Cell Nuclear Antigen; Homologous recombination; Humans; RNA-Binding Protein FUS; DNA-polymerasa III; Reconstitution; D-loop; jednovláknová DNA; homologní rekombinace; Rad51 Recombinase; DNA-dependentní DNA-polymerasy; DNA Polymerase III; protein FUS vázající RNA; TLS polymerases; HeLa buňky; lidé